Using fitness trackers to increase physical activity in a US Army health initiative. (December 2021) - Brown, Jill A; Whittaker, Kerry S; Hawkins, Stacy Ann; Jackson Santo, Theresa; Teyhen, Deydre S
Objective: Fitness trackers are appealing in public health intervention programmes aimed at promoting physical activity, but it is unclear whether tracker use leads to health behaviour change in soldiers. This programme evaluation investigated the effects of fitness tracker usage on goal-setting, self-monitoring and physical activity behaviours in soldiers participating in a 6-month pilot health promotion programme focused on improving sleep, activity and nutrition behaviours. Design: Participants in this programme ( n = 4, 418) were assigned to a health education, an education plus fitness tracker or a comparison (i.e. no intervention) condition. Data were collected at baseline, 3 and 6 months. Setting: Soldiers in five brigades participated in one of the three conditions, with health education integrated into daily operations. Method: Participants in the health education and education plus fitness tracker conditions were exposed to materials distributed via health educators and through leader interaction. Participants in the education plus fitness tracker condition were also assigned a fitness tracker for use. Results: Self-monitoring increased in all conditions over time; however, there was a significant interaction of group by time, such that individuals in the fitness tracker condition reported significantly greater increases in self-monitoring over time, compared with the other groups. Conversely, self-reported physical activity decreased in all conditions over time, with no significant interaction, indicating no effect of group membership. Conclusion: Although fitness trackers are popular in the health and fitness industry, they may have limited utility as a public health intervention aimed at increasing physical activity in soldiers participating in this programme.